Kebijakan Pemerintah Indonesia dalam Pencegahan Penyebaran Corona Virus Disease 2019 (Covid-19) Perspektif Maqashid Syari’ah - Anshor, Ahmad Muhtadi; Muttaqin, Muhammad Ngizzul (Institut Agama Islam Negeri Curup, 2020)
This study aims to provide an overview of several Indonesian government policies relate to prevent the spreading of Covid-19 from the perspective of maqashid syari'ah. This is due to the spreading of Covid-19 in Indonesia which has had several negative impacts. One of the negative impacts is to pose a threat to human existence, namely threatening human life and life. This condition requires the Indonesian government to issue various policies as an effort to prevent the spreading of Covid-19. This study uses a qualitative method with discourse analysis that discusses the legal-socio-contextual side of Indonesian government regulations and policies related to the prevention of the spreading of Covid-19 from the perspective of maqashid syari'ah. The findings of this study show, first, that all Indonesian government policies in the context of preventing the spreading of Covid-19 are a manifestation of maqashid syari'ah, namely as an effort to protect human existence as well as the embodiment of personal and group interests. Second, the realization of mashlahah as the essence of maqashid syari'ah can be realized by the existence of cooperation between the central and regional governments and the community to comply with and implement all government policies as a whole.